2020
DOI: 10.3390/ijms21072572
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Invasive Tool for Real-Time Measurement of Sulfate in Living Cells

Abstract: Sulfur (S) is an essential element for all forms of life. It is involved in numerous essential processes because S is considered as the primary source of one of the essential amino acids, methionine, which plays an important role in biological events. For the control and regulation of sulfate in a metabolic network through fluxomics, a non-invasive tool is highly desirable that opens the door to monitor the level of the sulfate in real time and space in living cells without fractionation of the cells or tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Furthermore, MD simulations provide a plausible explanation for these results by revealing how the β‐bulge residues gate sulfate entry and coordination near the chromophore. To our knowledge, SulfOFF‐1 is a unique example of a fluorescent sulfate sensor that holds promise for sulfate detection in complex aqueous applications ranging from environmental samples, biological fluids, and even living cells [49–54] . Together our data provides a rare glimpse of an intrinsic fluorescent protein sensor mechanism that could be generalized to other systems, warranting further exploration.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, MD simulations provide a plausible explanation for these results by revealing how the β‐bulge residues gate sulfate entry and coordination near the chromophore. To our knowledge, SulfOFF‐1 is a unique example of a fluorescent sulfate sensor that holds promise for sulfate detection in complex aqueous applications ranging from environmental samples, biological fluids, and even living cells [49–54] . Together our data provides a rare glimpse of an intrinsic fluorescent protein sensor mechanism that could be generalized to other systems, warranting further exploration.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the results of prokaryotic and eukaryotic studies suggested that the binding of NO 3 − with NrtA induces a conformational change, which results in increased fluorescence intensity of YFP and decreased fluorescence intensity of CFP, i.e., the change in the FRET ratio occurs in response to ligand (NO 3 − ). Similar sensors have been established for other nutrients and ions such as sulfate, 24 phosphate, 27 potassium, 28 etc. Previously, stable isotope techniques and radiotracers have been employed for flux analysis and cellular transport processes, but they lack cellular and subcellular spatio-temporal resolution.…”
Section: ■ Discussionmentioning
confidence: 91%
“…Moreover, the results of prokaryotic and eukaryotic studies suggested that the binding of NO 3 – with NrtA induces a conformational change, which results in increased fluorescence intensity of YFP and decreased fluorescence intensity of CFP, i.e., the change in the FRET ratio occurs in response to ligand (NO 3 – ). Similar sensors have been established for other nutrients and ions such as sulfate, phosphate, potassium, etc. Previously, stable isotope techniques and radiotracers have been employed for flux analysis and cellular transport processes, but they lack cellular and subcellular spatio-temporal resolution. , FRET-based genetically encoded nanosensors pave the way to dynamic quantification of metabolite with cellular and subcellular resolution in a nondestructive manner. , The response of our FLIP-NT nanosensor elucidated that the designed nanosensor has the potential for the quantification of flux or to measure transport across the intracellular membranes that could help the researchers to identify the dynamic of nitrate, underlying processes, and their regulatory switch.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, SulfOFF-1 is a unique example of a fluorescent sulfate sensor that holds promise for sulfate detection in complex aqueous applications ranging from environmental samples, biological fluids, and even living cells. [47][48][49][50][51] Together our data provides a rare glimpse of an intrinsic fluorescent protein sensor mechanism that could be generalized to other systems, warranting further exploration. Looking forward, we are excited by the possible outcomes from our collaborative approach to guide the design of proteinbased hosts for anions to achieve supramolecular functions in aqueous environments.…”
mentioning
confidence: 99%